UPAYA MENINGKATKAN HASIL BELAJAR IPS MELALUI PENGGUNAAN MEDIA PETA DI KELAS V SDN 011 TELUK PULAI - Baharuddin Baharuddin (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2017)
This study aims to describe learning outcomes by using the map media. The subjects of the study were students of grade V SDN 011 Teluk Pulai consisting of two cycles. Improvement of learning outcomes in this study in terms of four categories, namely the ability to absorb, the effectiveness of learning, mastery of student learning both mastery of individual and classical completeness, and mastery of learning outcomes. Instruments used for data collection are oral tests and written tests in the form of LKS conducted after the learning process. The results showed that the average learning achievement 83% is categorized very well, the effectiveness of learning is categorized very effective with an average of 8.5, while the students' learning result completeness is 100% complete. Based on the results above research can be concluded that through the media map can improve learning outcomes IPS SDN 011 Teluk Pulai.